Lulwoana sp., a dark septate endophyte in roots of Posidonia oceanica (L.) Delile seagrass. (29th September 2014) - Torta, L.; Lo Piccolo, S.; Piazza, G.; Burruano, S.; Colombo, P.; Ottonello, D.; Perrone, R.; Di Maida, G.; Pirrotta, M.; Tomasello, A.; Calvo, S.; Franken, P.
Abstract Posidonia oceanica is the most common, widespread and important monocotyledon seagrass in the Mediterranean Basin, and hosts a large biodiversity of species, including microorganisms with key roles in the marine environment. In this study, we ascertain the presence of a fungal endophyte in the roots of P. oceanica growing on different substrata (rock, sand and matte) in two Sicilian marine meadows. Staining techniques on root fragments and sections, in combination with microscope observations, were used to visualise the fungal presence and determine the percentage of fungal colonisation (FC) in this tissue. In root fragments, statistical analysis of the FC showed a higher mean in roots anchored on rock than on matte and sand. In root sections, an inter‐ and intracellular septate mycelium, producing intracellular microsclerotia, was detected from the rhizodermis to the vascular cylinder. Using isolation techniques, we obtained, from both sampling sites, sterile, slow‐growing fungal colonies, dark in colour, with septate mycelium, belonging to the dark septate endophytes (DSEs). DNA sequencing of the internal transcribed spacer (ITS) region identified these colonies as Lulwoana sp. To our knowledge, this is the first report of Lulwoana sp. as DSE in roots of P. oceanica. Moreover, the highest fungal colonisation, detected in P. oceanica roots growing on rock, suggests that the presence of the DSE may help the host in several ways, particularly in capturing mineral nutrients through lytic activity.